Mechanisms of action of the sodium‐glucose cotransporter‐2 (SGLT2) inhibitor canagliflozin on tubular inflammation and damage: A post hoc mediation analysis of the CANVAS trial. Issue 10 (28th June 2022) - Sen, Taha; Koshino, Akihiko; Neal, Bruce; Bijlsma, Maarten J.; Arnott, Clare; Li, Jingwei; Hansen, Michael K.; Ix, Joachim H.; Heerspink, Hiddo J. L.
Abstract: Aims: To test the hypothesis that the reduction in urinary kidney injury molecule‐1 (KIM‐1) observed with the sodium‐glucose cotransporter‐2 (SGLT2) inhibitor canagliflozin is mediated through its effects on urine albumin to creatinine ratio (UACR) and monocyte chemoattractant protein‐1 (MCP‐1) by assessing the proportion of the effect of canagliflozin on KIM‐1 that is mediated through its effects on MCP‐1 and UACR in patients with type 2 diabetes and albuminuric kidney disease. Material and methods: We measured KIM‐1 and MCP‐1 levels in urine samples from the CANVAS trial at baseline and Week 52 with the Mesoscale QuickPlex SQ 120 platform. KIM‐1 and MCP‐1 were standardized by urinary creatinine (Cr). The proportion of the effect of canagliflozin that is mediated through UACR and MCP‐1/Cr on KIM‐1/Cr was estimated with G‐computation. Results: In total, 763 patients with micro‐ or macroalbuminuria (17.6% of the total cohort) were included. Baseline characteristics were well balanced between the canagliflozin and placebo group. At Year 1, canagliflozin compared to placebo reduced UACR, MCP‐1/Cr and KIM‐1/Cr by 40.4% (95% CI 31.0, 48.4), 18.1% (95% CI 8.9, 26.4) and 30.9% (95% CI 23.0, 38.0), respectively. The proportion of the effect of canagliflozin on KIM‐1/Cr mediated by its effect on UACR and in turn on MCP‐1/Cr was 15.2% (95% CI 9.4, 24.5). Conclusion: Canagliflozin reduces urinary KIM‐1, suggesting decreased tubular damage. This effect was partly mediated through a reduction in MCP‐1, indicative of reduced tubular inflammation, which was in turn mediated by a reduction in UACR. This post hoc analysis suggests that urinary albumin leakage may lead to tubular inflammation and induction of injury, and provide mechanistic insight for how canagliflozin may ameliorate tubular damage, but further research is required to confirm these findings.